Audit Committee Expectations on the Effectiveness of the Internal Audit Function: A Malaysian Perspective - Lee, Soo Sin (Curtin University, 2017)
This study draws on a multi-theoretical lens to explore how the contextual and environmental factors have impacted on the internal audit practices of listed issuers in Malaysia. This study finds that listed issuers decouple the regulatory requirements to stay legitimate. Top management’s scepticism over value contribution of internal audit function has relegated its significant role in governance. A refined framework is developed incorporating the audit committee’s expectation on enhancement of the effectiveness of the internal audit function.